ANALISIS PERFORMANSI CLOSED THERMOSYPON DENGAN VARIASI KONSENTRASI CAMPURAN ASETON DAN ETANOL - Arif Rochman Fachrudin (Universitas Lambung Mangkurat, 2016)
Thermosypon are heat exchangers in the form of a pipe that consists of three main parts: evaporator (the bottom of the tube), adiabatic and condenser (top tube). Evaporator part is the part that receives heat and absorb them to be brought goto the condenser, the part which releases heat to the environment. Among the evaporator and condenser there is a section that separates, ie adiabatic section as part of an isolated so no temperature exchange with the pipe lingkungan.Didalam there is the working fluid that carries heat from the evaporator evaporator.Panas absorbed from the environment and move up the tube because of differences in density between the vapor and liquid to kesisi condensation (condenser) and heat dilepaskan.Pada side vapor condensation condensed into liquid and moves down back to the evaporator because of the force of gravity.In this study, thermosypon made of copper with a diameter of 12,7 mm and a length of 500 mm with a length of 195 mm condenser. The area subject to the evaporator as the heat source side, adiabatic section is isolated so that no heat exchange with the environment and the area condenser mounted heat sink which aims to remove heat from the heat pipe to the environment. The research was done by varying the concentration of the working fluid, the concentration of the mixture of acetone and ethanol.Variasi fluid mixture concentrations used in this study is the percentage of acetone to methanol, yaitu0%, 20%, 40%, 60%, 80% and 100%. The data required is the temperature at the evaporator (Te), the temperature of the condenser (TK1, Tk2, TK3) and air temperature (Tu).The results showed that, most small thermal prisoner at the time of the concentration of 100% acetone to ethanol. At the same acetone concentration, the higher the power (the higher the temperature), the greater the heat flux and power output. The process in this experiment the largest output power and capacity terbesarterjadi the acetone concentration of 100% and the highest power (63 W).